2023
DOI: 10.3390/su15108396
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Impacts of COVID-19 on Low-Income Households: Evidence from Malaysia

Abstract: This study unravelled the economic impacts of the coronavirus disease 2019 (COVID-19) on low-income households. The asymmetric economic impacts of the pandemic that are biased towards the poor, young, and women have been well established. However, micro evidence on the poor is limited, thus demanding detailed understanding to design an effective targeted assistance. In this study, data were gathered from face-to-face interviews using a sampling frame provided by the Department of Statistics Malaysia (DOSM). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…At the level of household income, cross-country evidence suggests that the poorest among the households benefited most from compensatory policy measures, while the disposable income of the best-placed households suffered less from containment measures [4][5][6]. Evidence from Malaysia indicated that households with low incomes were unaffected by pandemic restrictions or even benefited [7]. The same reference indicated that female-headed households suffered as much as male-headed households during the pandemic, as demonstrated in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 94%